ECTOPIC ADRENOCORTICAL TISSUE IN INGUINAL HERNIA SAC- AN INCIDENTAL FINDING - DR. SAVITRI M. NERUNE; DR.B.R.YELIKAR; DR.AMRUTHA MR; DR. SHRUTI KULKARNI (International Journal of Pharma and Bio Sciences, 2016)
Ectopic adrenal tissue is reported near adrenal gland, kidney, retroperitoneum and hilus of gonads. It is common among the pediatric age group and rarely encountered in adults. Ectopic adrenal tissue in hernia sac is a rare finding. Here we report a case of ectopic adrenocortical tissue which was identified incidentally on microscopic examination of inguinal hernia sac in twenty seven year old man.